2022
DOI: 10.1039/d2dt00337f
|View full text |Cite
|
Sign up to set email alerts
|

Highly-fluorescent BODIPY-functionalised metallacages as drug delivery systems: synthesis, characterisation and cellular accumulation studies

Abstract: With the aim of designing new metallosupramolecular architectures for drug delivery, research has focused on porous 3-dimentional (3D)-metallacages able to encapsulate cytotoxic agents protecting them from metabolism while targeting them...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…BODIPY is another recurrent structural moiety that is often incorporated into different ligands to confer them luminescent properties that they would not otherwise display. In a recent example, Casini et al have reported the synthesis of two different ligands 133 , L1 and L2, shown in Figure 38 , that contain the BODIPY fragment covalently bonded [ 115 ]. Using standard methods, they prepared the Pd 2 (L 1,2 ) 4 cages 134 , which resulted as strongly emissive due to the presence of the BODIPY luminophore.…”
Section: Systems Composed By Metallacages Pd X L ...mentioning
confidence: 99%
See 2 more Smart Citations
“…BODIPY is another recurrent structural moiety that is often incorporated into different ligands to confer them luminescent properties that they would not otherwise display. In a recent example, Casini et al have reported the synthesis of two different ligands 133 , L1 and L2, shown in Figure 38 , that contain the BODIPY fragment covalently bonded [ 115 ]. Using standard methods, they prepared the Pd 2 (L 1,2 ) 4 cages 134 , which resulted as strongly emissive due to the presence of the BODIPY luminophore.…”
Section: Systems Composed By Metallacages Pd X L ...mentioning
confidence: 99%
“…The complexes thus prepared are stable in physiological conditions and also are able to encapsulate efficiently metallodrugs such as cisplatin. This ability and the notable luminescence shown by the cages prompted in-depth and successful research about their cellular uptake and distribution in different types of cancer cells by fluorescence microscopy [ 115 ]. This is an area of research undergoing a really fast growth, due to the enormous possibilities and social impact [ 116 ].…”
Section: Systems Composed By Metallacages Pd X L ...mentioning
confidence: 99%
See 1 more Smart Citation
“…3A) [64]. In a different approach, the tethering of luminophores in the outer structure of Pd 2 L 4 metallacages (L = 3,5-bis(3-ethynylpyridine)phenyl) has been used to unravel their intracellular distribution and uptake mechanisms [68][69][70]. Organic luminophores can also be modified to generate luminescent ligands capable to assemble into SCCs, as demonstrated by the boron dipyrromethene (BODIPY)-based metallacycles reported by Gupta et al [71,72].…”
Section: Biomedical Applications Of Sccsmentioning
confidence: 99%
“…32 Imaging of nanospheres in vivo remains, due to the so called "heavy atom effect", a problem and only a few uorescent M 2 L 4 spheres have been reported. [33][34][35] Although, some M 2 L 4 nanospheres have shown to be uorescent, biological application requires a good uorescent quantum yield and an emission wavelength preferably in the red light. Unfunctionalized nanospheres typically absorb and emit between 250 and 400 nm, which is impractical due to the absorption of living matter (e.g., proteins) in the same region.…”
Section: Introductionmentioning
confidence: 99%